2015
DOI: 10.1186/s13058-014-0507-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells in newly diagnosed inflammatory breast cancer

Abstract: IntroductionCirculating tumor cells (CTCs) are an independent prognostic factor for progression-free survival (PFS) and overall survival (OS) in patients with metastatic breast cancer. Inflammatory breast cancer (IBC) is one of the most aggressive forms of breast cancer. The prognostic value of a CTC count in newly diagnosed IBC has not been established. The aim of this study was to assess the prognostic value of a baseline CTC count in patients with newly diagnosed IBC.MethodsThis retrospective study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
1
29
1
Order By: Relevance
“…Although the breast cancers examined were not metastatic with the likely possibility of a low and difficult to detect frequency of CTCs, the present study revealed a relatively higher sensitivity (90.76%) in CTC detection of breast cancer compare with the sensitivity of 54.5% in a previously study (8), in which CTC were detected using CELLSEARCH ® system. The high sensitivity of CTC detection in breast cancer were identical to that of other solid tumors evaluated with the iFISH system, including gastric (90.5%) (15), lung (92%) and esophageal (87%) cancer (5).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Although the breast cancers examined were not metastatic with the likely possibility of a low and difficult to detect frequency of CTCs, the present study revealed a relatively higher sensitivity (90.76%) in CTC detection of breast cancer compare with the sensitivity of 54.5% in a previously study (8), in which CTC were detected using CELLSEARCH ® system. The high sensitivity of CTC detection in breast cancer were identical to that of other solid tumors evaluated with the iFISH system, including gastric (90.5%) (15), lung (92%) and esophageal (87%) cancer (5).…”
Section: Discussioncontrasting
confidence: 71%
“…In metastatic breast cancer, the Food and Drug Administration approved the CELLSEARCH ® system for routine clinical use in guiding clinical management (7). However, few studies (4,8) have been published in CTC detection for breast cancer prior to metastasis. Mammaglobin-positive CTC detection has previously been performed in women suspected of breast cancer; however, it failed to detect intraductal cancer and 50% of in situ cancers (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, epithelial and mesenchymal patterns were different across tumor subtypes and were also dynamic during therapy, mesenchymal CTC being frequently observed at the time of tumor progression. Several other studies reported some mesenchymal traits on detected BC CTC (Armstrong et al., 2011; Mego et al., 2015a,b, 2012; Papadaki et al., 2014), but the clinical impact of these cells has not been demonstrated yet. Stemness‐related features have been also detected on BC CTC (Raimondi et al., 2011).…”
Section: Biology Of Ctcsmentioning
confidence: 96%
“…CTC count among 147 patients with IBC reached 179 and 249 CTCs/7.5 mL blood for patients with stage III and metastatic IBC, respectively (71). IBC patients with CTCs in the peripheral blood had abnormalities in adaptive immunity that may impact tumor cell dissemination (72). IBC carcinoma tissues exhibit marked monocytes/ macrophages infiltrates localized around tumor emboli (73).…”
Section: Sclc and Ctcsmentioning
confidence: 99%